Depression and anxiety among children and adolescents pre and post COVID-19: A comparative meta-analysis - Wang, Sifan; Chen, Lin; Ran, Hailiang; Che, Yusan; Fang, Die; Sun, Hao; Peng, Junwei; Liang, Xuemeng; Xiao, Yuanyuan (Frontiers in Psychiatry, 2022)
Background Published studies in comparing pre and post the COVID-19 pandemic depression and anxiety levels among children and adolescents yielded incongruent results. Therefore, there is a necessity to perform a timely meta-analysis to synthesize existing evidence. Methods A total of 10 digital databases (PubMed, Web of Science, PsycINFO, the Cochrane Library, Embase, Scopus, ScienceDirect, CNKI, WanFang, CQVIP) were fully searched for eligible studies published before November 6, 2021. Based on quality assessment results, relevant data were extracted for eligible studies of higher quality. We combined standardized mean difference (SMD) or prevalence ratio (RR) for anxiety and depression pre and post the COVID-19 pandemic by using random-effects models. Sensitivity analysis was further performed to evaluate heterogeneity of included studies. Results 14,508 articles were preliminarily identified, and after stepwise screening process, 8 articles were included eventually. The results showed that the SMD for post COVID-19 anxiety score measured by GAD-7 was 0.12 (95% CI: 0.08, 0.17), an significant increase compared with pre COVID-19 period; the SMDs and 95% CIs for post COVID-18 depression scores measured by PHQ-9, PHQ-8, and MFQ were 0.17 (95% CI: 0.10, 0.24), 0.23 (95% CI: 0.08, 0.38), and 0.11 (95% CI: 0.06, 0.17), respectively, also significantly increased compared with pre COVID-19 period. The RR for depression was 2.54 (95% CI: 2.48, 2.60) in post COVID-19 period when compared with pre-pandemic. Conclusions Children and adolescents reported deteriorated anxiety and depression levels after the COVID-19 pandemic. More attention should be paid to this vulnerable group. Effective, expedient, and practical intervention measures which are compatible with COVID-19 prevention and control policies should be developed and implemented to maintain mental health wellbeing of the youths.